Language Shift, Language Death and Multilingualism: A Review of Case Studies - Marwa Mohammad Masood (Indonesian TESOL Journal, 2023)
Language shift causes threat to the existing languages in a community, especially those already endangered (Musgrave, 2014). Once threatened, these endangered languages go through the unfortunate process of extinction over time (Natsir and Lubis, 2021). Language death occurs when three of its most crucial values go extinct one by one. The three elements are- “loss of function”, “loss of prestige” and finally “loss of competence” (Kornai. 2013). A language goes completely extinct when last speaker of the language expires. This paper focuses on the dominating factors that result in the death of languages in different communities around the globe and illustrates a few case studies of particular communities where a major language shift occurred which simply replaced or resulted in the death of one of the most spoken languages with another politically and socially powerful one. The paper ends by mentioning a case study where effective steps helped to revive a dead language and successfully made it a widely spoken language by the people of a community.